RSSI variability characterization and calibration method in wireless sensor network - Zhen Fang; Zhan Zhao; Daoqu Geng; Yundong Xuan; Lidong Du; Xunxue Cui (2010 International Conference on Information and Automation, 2010)
Positioning is a fundamental issue for wireless sensor network operation. The Received Signal Strength Indication (RSSI) of a radio channel provides a feasible way of estimating distance between sensor nodes as they need not any additional hardware but a radio transceiver. The main drawback of using RSSI is its instability and interference susceptibleness noticed in real environments. There has been a lack of comprehensive characterization of fundamental factors contributing to RSSI variability from the radio irregularity constraint of RSSI localization algorithms. Base on SKLTT sensor nodes designed by our research group, a characterization description is provided about radio signal strength properties of the CC2420 communication chip by using a monopole antenna in the paper. The RSSI variability is modeled and analyzed from node consistency and non-isotropic signal propagates, and subsequently the corresponding calibration measures are given. Some experiments are shown that RSSI can work well about the localization variability performance for specially instrumented scenarios, such as an ideal open, outdoor environment, after strict selection of sensor nodes and calibration. The results show that RSSI calibration measurements can be successfully applied to localization in sensor networks.